Baseline Assessment of Petroleum Contamination and Soil Properties at Contaminated Sites in Utqiavik, Alaska - Barbato,Robyn A; Jarvis,Stacey L; Foley,Karen L; Jones,Robert M (2017)
Elevated contamination levels persisted for decades at the former Naval Arctic Research Station at two sites in particular, the Airstrip and Powerhouse sites. Because of the challenging environmental conditions at these sites, physical and chemical remediation technologies have not been effective at reducing petroleum contamination levels. Therefore, the continued presence of the contamination warranted a deeper investigation of petroleum chemistry, soil attributes, and biological activity at these sites. Petroleum chemistry analysis revealed the heterogeneous contamination at each site, with higher levels observed at the upgradient sites, which were situated further from the nearby freshwater Imikpuk Lake. Additionally, soil biological data tests showed an active microbial community, including high bacterial numbers in these soils. The results from this baseline study indicate that stimulating biodegradation processes in petroleum-contaminated soils is a promising technology for bioremediation.